Effect of a Multistage Educational Skill-Based Program on Nurse's Stress and Anxiety in the Intensive Care Setting: A Randomized Controlled Trial - Saffari, Mohsen (Behav Neurol, 2021)
BACKGROUND: Psychological problems such as stress and anxiety are prevalent among working nurses in the intensive care units (ICUs). This study was aimed at investigating the effects of three skill-based educational programs on stress and anxiety among critical care nurses. METHODS: Using a randomized controlled trial, 160 nurses were assigned to four groups including one control and three intervention groups. A standard skill-based educational program was delivered to three intervention groups using booklet, booklet+oral presentation, and booklet+oral presentation+clinical teaching over a period of one month to reduce different types of stress and anxiety. The control group received routine education only. Perceived stress, state anxiety, trait anxiety, and work-related stress were assessed at baseline and three times after the intervention (15 days, 3 months, and 21 months). Repeated-measure analysis of variance was used for data analysis. RESULTS: There was no significant change in the control group in terms of study variables during follow-up assessments, whereas measures of stress and anxiety were reduced after intervention in the trial groups except trait anxiety. Nurses in the mixed-method group (booklet+oral presentation+clinical teaching) showed less stress and anxiety during follow-ups. Although the stress and anxiety scores decreased in the first and second follow-ups, there was no significant reduction in the third follow-up. CONCLUSIONS: To improve the mental health and performance of the intensive care unit nurses, knowledge-based and skill-based training programs seem useful. Continuous training may help to maintain the effectiveness of these programs over time.